2007
DOI: 10.1038/sj.bjc.6603708
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori eradication for low-grade gastric mucosa-associated lymphoid tissue lymphoma is more successful in inducing remission in distal compared to proximal disease

Abstract: A series of studies has shown that Helicobacter pylori eradication induces remission in most patients with low-grade gastric mucosaassociated lymphoid tissue (MALT) lymphoma. However, there have been few reports about the effect of bacterial treatment on the gastric MALT lymphoma in Korea, a well-known H. pylori endemic area. A total of 111 H. pylori-infected patients were prospectively enrolled in Seoul National University Hospital and 99 among them were completely followed up according to our protocol. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 19 publications
2
35
0
1
Order By: Relevance
“…The location of the lesion is one of the factors associated with efficacy. Kim et al (2007) have reported that in H. pylori-infected gastric MALT lymphoma patients, those with distal lesions had higher CR rates (92.5%) than those with proximal lesions (CR rate 65.5%). We also observed the same tendency in H. pylori-negative MALT lymphoma patients, among whom only the responders had antral lesions, but this tendency did not show statistical significance due to the limited number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The location of the lesion is one of the factors associated with efficacy. Kim et al (2007) have reported that in H. pylori-infected gastric MALT lymphoma patients, those with distal lesions had higher CR rates (92.5%) than those with proximal lesions (CR rate 65.5%). We also observed the same tendency in H. pylori-negative MALT lymphoma patients, among whom only the responders had antral lesions, but this tendency did not show statistical significance due to the limited number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 29 trials were finally included , whilst the remaining 12 studies were excluded due to lack of either treatment option chosen or treatment efficacy following H. pylori eradication therapy failure [38][39][40][41][42][43][44][45][46][47][48][49]. Among the 29 trials included in this pooled-data analysis, the study design was prospective in 21 series and retrospective in the remaining eight series.…”
Section: Descriptive Analysismentioning
confidence: 99%
“…In recent years, several large‐scale studies have investigated the efficacy of H. pylori eradication therapy against gastric MALT lymphoma. Among previous studies with around 100 subjects, CR was achieved in 80% (96/120) in a German multicenter prospective study,17 94% (85/90) in a Korean prospective study,18 85% (84/99) in a Korean single‐center prospective study,19 74% (146/196) in a German single‐center retrospective study,20 76% (78/102) in a joint Swiss‐Italian retrospective study,21 77% (323/420) in a Japanese retrospective study,15 and 83% (78/94) in a Portuguese single‐center retrospective study 22. However, CR criteria varied among those studies.…”
Section: Discussionmentioning
confidence: 84%
“…Relapse of gastric MALT lymphoma was recorded in 64 of the 852 patients who achieved CR (7.5%), and treatment failure (relapse, PD, and/or non‐CR at ≥6 months after successful H. pylori eradication) was observed in 144 of all 1055 patients (13.6%). Table 3 summarizes 8 prospective studies,17, 18, 19, 30, 31, 32, 33 including the present investigation, of 47‐120 patients. The present study (n = 97) represents the third largest among these prospective studies.…”
Section: Discussionmentioning
confidence: 99%